Failure is an option: an innovative engineering curriculum. Issue 3 (10th May 2018) - Simpson, Edward; Bradley, David; O'Keeffe, Juliette
Abstract : Purpose: Advancements and innovation in engineering design are based on learning from previous failures but students are encouraged to "succeed" first time and hence can avoid learning from failure in practice. The purpose of this paper is to design and evaluate a curriculum to help engineering design students to learn from failure. Design/methodology/approach: A new curriculum design provided a case study for evaluating the effects of incorporating learning from failure within a civil engineering course. An analysis of the changes in course output was undertaken in relation to graduate destination data covering 2006 to 2016 and student satisfaction from 2012 to 2017 and a number of challenges and solutions for curriculum designers were identified. Findings: The design and delivery of an innovative curriculum, within typical constraints, can provide opportunities for students to develop resilience to failure as an integral part of their learning in order to think creatively and develop novel engineering solutions. The key issues identified were: the selection of appropriate teaching methods, creating an environment for exploratory learning, group and team assessments with competitive elements where practicable and providing students with many different pedagogical approaches to produce a quality learning experience. Originality/value: This case study demonstrates how to design and implement an innovative curriculum that can produce positive benefits of learning from failure. This model can be applied to other disciplines such as building surveying and construction management. This approach underpins the development of skills necessary in the educational experience to develop as a professional building pathologist.